Limnological features of Pandoh reservoir, Himachal Pradesh - Kaushal, D K; Joshi, H C; Kumar, S (Indian Journal of Fisheries, 2011)
Pandoh reservoir, a 200 ha impoundment situated across the river Beas in thedistrict Mandi, Himachal Pradesh was surveyed for its limnological features.The low values of total alkalinity (24-44 ppm), specific conductivity (86.4â€”97.2|j,mhos/cm), low temperature regime (10.5-16.5Â°c) and nutrient status point towardstemperate condition and oligotrophic tendencies of the reservoir . This isstrengthened by the poor plankton count. Suggestions pertaining to managementand development of the fisheries in the reservoir were made.